A rare case report on molar heterotopic pregnancy - Mandrupkar, Tejasi C.; Tambe, Sanjaykumar G.; Padore, Ishaan S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A 34 y/o G4P3L3, with 1.5 months of amenorrhoeas, presented with complaints of pain in abdomen and vaginal spotting. Patient was diagnosed as a case of heterotopic pregnancy with ruptured ectopic on USG. The patient had her left oviduct removed by means of exploratory laparotomy, followed by dilatation and evacuation of retained products of conception in the uterus. The presented case highlights the importance of meticulously performed ultrasound examination. Also, the visualization of a normal intrauterine pregnancy in the ultrasound examination does not exempt the examiner from a need of distinct imaging of the adnexa. The case also conveys the importance of histological examination of products of conception which helps to confirm an appropriate diagnosis, thereby the obstetrician can offer appropriate treatment, counselling and follow up to the patient. Early diagnosis of this pathology decreases the risk of complication incidence as well as maternal mortality.